Arabinoxylan from Plantago ovate (Husk) a novel binder and superdisintegrant - Erum, Alia; Bashir, Sajid; Saghir, Shazia; Sarfraz, Rai Muhammad (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The aim of the present investigation was to evaluate the binding and disintegrating properties of arabinoxylan isolated from Ispaghula (Plantago ovata) husk. Atenolol and atorvastatin orodispersible tablet F1, F2 and F3 were prepared by direct compression method using arabinoxylan (12, 9, 6) mg as superdisintegrant, and F4 and F5 containing 12 mg Ispaghula husk and 12 mg sodium starch glycolate, respectively. Metformin tablets were prepared by wet granulation method F1 containing starch as binder, F2 containing arabinoxylan as binder and F3 containing arabinoxylan as binder and as superdisintegrant. Prepared tablets were evaluated for precompression parameters such as compatibility studies, bulk density, tapped density, angle of repose, Hausners ratio and Cars index and post compression parameters such as weight variation, hardness, thickness, diameter, wetting time, water absorption ratio disintegration time drug release and moisture uptake studies. Attempts were done to trace the possible disintegrant mechanism of arabinoxylan. FTIR spectra of physical blend of atenolol, atorvastatin, metformin with arabinoxylan confirmed the compatibility of excepient with formulation ingredients. All the formulations of atenolol, atorvastatin satisfied the limits of redispersion with a dispersion time of less than 60 sec. F1 showed minimum disintegration time 4 sec providing the evidence of arabinoxylan an excellent superdisintegrant when compared with F4 containing Ispaghula husk with disintegration time 30 sec and F5 contains sodium starch glycolate having disintegration time of 35 sec. Minimum wetting time of 17 sec and high water absorption ratio of F1 formulation confirmed the arabinoxylan as swelling disintegrant. The results of metformin tablet indicate that arabinoxylan could be useful to produce tablets with desired characteristics for specific purposes, and could be used as an alternative substitute binder and superdisintegrant in pharmaceutical industries. These studies provide a strong evidence for usefulness of arabinoxylan as binder and superdisintegrant and a good alternative to natural and synthetic superdisintegrant. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21891 Dhaka Univ. J. Pharm. Sci. 13(2): 133-141, 2014 (December)